A Systematic Literature Review in Cross-browser Testing - Sabaren, Leandro N. (2018)
Many users access web pages from different browsers looking for the same user experience in all of them. However, there are several causes that produce compatibility issues. Those defects affect functionalities and user interface components. In this paper we present a systematic literature review which aims to find and summarize existing techniques, tools and challenges related to crossbrowser testing. According to the results, the most used technique is the visual analysis. However, there are still challenges to face. The most important challenge is the identification of dynamic components in the user interface. Cross-browser compatibility topics are getting importance according to an increment in published articles. Nevertheless, there are techniques that are not completely developed yet and do not fully support test automation practices.